Solidarity like means of compensation for damage in Africa to the concept of insurance : the case of Benin and Mauritania - (:unkn) unknown (My University, 2017)
Since the dawn of times, whatever the shape it has had, one of the major worries of mankind has been and still is his protection, the protection of the people close to him and that of his belongings against the hardship of life. In that perspective, Insurance companies have been created.In Africa, before the introduction of that notion, it is the solidarity in its various forms (assabiya, touiza, Iahwa or else tontine) that has served as means to repair damage.Insurance law that has for mission to govern the activity, has, in Africa a configuration that was intimately connected to the colonial history. The study of the evolution of the notion of insurance in Mauritania and in Benin puts us in front of two legal systems having peculiarities sometimes stemming from the islamic law or common law. However, the point of convergence of these two systems remains the French law which they inherited via colonization. This imported law has it been learned by these two countries?The CIMA code and the Mauritanian insurance code will allow us to fully grasp the insurance contrat, the compensation and the activity of insurance : essential elements to raise the current situation of the sector of the insurances in Benin and in Mauritania. In Africa, even if in certain countries the sector of the insurance is in net growth, the questions raised by this thesis will be relative to the adaptability of the conventional insurance in the African countries in which the sector of insurance has difficulty developing.In any case, it will be necessary to lead a reflexion on alternatives of the developement in Africa of the conventional insurance.
Keywords: African Research